THE INFLUENCE RELIGIOSITY, LIFESTYLE, PRICE, AND FASHION TRENDS ON MUSLIM FASHION PURCHASE DECISIONS (A CASE STUDY OF GENERATION Z IN MEDAN CITY) - Puspita, Ditiya (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This study aims to analyze the influence of religiosity, lifestyle, price, and fashion trends on Muslim fashion purchasing decisions by Generation Z in Medan City. The method used is a quantitative approach with SEM-PLS analysis techniques through SmartPLS 4 software and involving 100 respondents. The results show that religiosity, lifestyle, and fashion trends have a significant influence on purchasing decisions, while price does not show a significant influence. The R² value of 57.3% indicates that the model can explain more than half of the variation in purchasing decisions. This finding reflects that Gen Z prioritizes religious aspects and lifestyle over price considerations, which is in line with the principles of consumption in Islamic economics namely, orientation towards needs, ethical values, and compliance with sharia.Keywords: Muslim fashion, religiosity, lifestyle, price, fashion trends, purchasing decisions